Conceptual basis of preventive counselling in patients with chronic non-communicable diseases and their risk factors - A. M. Kalinina (Кардиоваскулярная терапия и профилактика)
The paper presents the results of an analytical study on the complex problem of preventive counselling in patients with multifactorial chronic non-communicable diseases (CNCD). Based on the extensive experience of the author and the major external sources of evidence, the conceptual principles of preventive counselling are presented for people with CNCD or CNCD risk factors (RFs), according to individual personality traits and behavioural specifics. The key requirements for the development of preventive counselling algorithms focusing on major behavioural RFs are identified, which opens a new perspective in the CNCD prevention.